Analysis of the Implementation of Digital Warehouse Systems in Supporting Operational Efficiency and Inventory Accuracy - A. Putri Djohar Tenri Waru; Yunita Janah; Idah Yuniasih (EDUJAVARE: International Journal of Educational Research, 2026)
Advances in information technology and digital transformation have driven companies to make changes across various aspects of their business operations, including warehouse and inventory management systems. This research aims to analyze the implementation of a digital warehouse system in supporting operational efficiency and inventory accuracy at XYZ Distribution Company, as well as to identify obstacles and its optimization strategies. The method used is descriptive qualitative with a case study approach. Primary data were obtained through observation and semi-structured interviews with the operational manager and warehouse staff, while secondary data came from internal company documents. The results show that the transition from manual recording to a digital system integrates the workflow centrally. Digitalization successfully reduced item search time from 15–20 minutes to be much more efficient, resolved bottlenecks in the picking area, and accelerated the stock opname process. Furthermore, inventory accuracy increased significantly, marked by a drastic decrease in inventory discrepancy from 2,789 units in 2022 to 250 units in 2025. The main obstacle faced is that barcode scanning technology has not been adopted, so data input is still performed manually and leaves potential for human error. The company's mitigation strategy is carried out through tightening SOPs in the form of a double-checker system and product specification coding standardization.